2013
DOI: 10.1352/1934-9556-51.5.376
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Science of Employment and Economic Self-Sufficiency for People With Intellectual and Developmental Disabilities

Abstract: Employment, career advancement, and financial independence are highly valued in the United States. As expectations, they are often instilled at a young age and incentivized throughout adulthood. Despite their importance, employment and economic sufficiency continue to be out of reach for most people with intellectual and developmental disabilities (IDD). Over the last quarter century, extensive research and effort has been committed to understanding and improving these phenomena. This paper summarizes this emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 24 publications
2
23
0
4
Order By: Relevance
“…The U.S. Department of Labor estimates that the civilian labor force participation in the United States is approximately 63.2% as of March 2014. The more current Oklahoma data (2004 and 2009) are below the national figures, a finding consistent with other reports of the employment opportunities for persons with disabilities (Nord, Luecking, Mank, Kiernan, & Wray, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The U.S. Department of Labor estimates that the civilian labor force participation in the United States is approximately 63.2% as of March 2014. The more current Oklahoma data (2004 and 2009) are below the national figures, a finding consistent with other reports of the employment opportunities for persons with disabilities (Nord, Luecking, Mank, Kiernan, & Wray, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…They also provide supported employment programs to help individuals with disabilities find and maintain competitive jobs of their choice that provide the same work settings and same pay rates enjoyed by persons without disabilities. They become more independent, self-supporting, and more thoroughly integrated into their communities [6]. Data analysis confirms for us that a relatively small group of Medicaid beneficiaries with MH/SUD/IDD service needs account for a disproportionately large amount of Medicaid spending.…”
Section: Enhancing Care For Persons With Smi Sud and Iddsupporting
confidence: 55%
“…Social, cultural, and political practices may all influence this finding. One significant barrier continues to be the financial incentives to earn a lower wage to qualify for benefits such as Medicaid or Social Security Income (SSI; Butterworth et al, 2015;Nord, Luecking, Mank, Kiernan, & Wray, 2013). In their national report on employment services and outcomes, Butterworth et al (2015) found that employment for individuals with disabilities receiving SSI reached a 20-year low in 2013 (4.3%).…”
Section: Discussionmentioning
confidence: 99%